Unconventional genetic code systems in archaea - Meng, Kexin; Chung, Christina Z.; Söll, Dieter; Krahn, Natalie (Frontiers in Microbiology, 2022)
Archaea constitute the third domain of life, distinct from bacteria and eukaryotes given their ability to tolerate extreme environments. To survive these harsh conditions, certain archaeal lineages possess unique genetic code systems to encode either selenocysteine or pyrrolysine, rare amino acids not found in all organisms. Furthermore, archaea utilize alternate tRNA-dependent pathways to biosynthesize and incorporate members of the twenty canonical amino acids. Recent discoveries of new archaeal species have revealed the co-occurrence of these genetic code systems within a single lineage. This review discusses the diverse genetic code systems of archaea, while detailing the associated biochemical elements and molecular mechanisms.